Delayed manifestation of COVID-19 presenting as lower extremity multilevel arterial thrombosis: a case report. Issue 6 (19th November 2020) - Schweblin, Cecilia; Hachulla, Anne Lise; Roffi, Marco; Glauser, Frédéric
Abstract: Background: Venous thrombo-embolic events have been described in hospitalized patients with coronavirus disease 2019 (COVID-19), suggesting the presence of coagulopathy induced by the viral infection. To date, only rare cases of arterial thrombosis related to COVID-19 have been reported. Case summary: A 54-year-old patient with an influenza-like illness 15 days earlier, which resolved, and no known cardiovascular risk factor presented with acute right lower limb ischaemia. A computed tomography angiogram of the abdominal aorta and lower extremities showed, in the absence of vascular disease, a subocclusive thrombosis of the right common iliac artery and an occlusion of the right internal iliac, profunda femoral, and popliteal arteries. On the left side, the computed tomography angiogram demonstrated a non-occlusive thrombosis of the common femoral artery. The patient underwent emergency surgical thrombectomy as well as endovascular revascularization on the right side followed by therapeutic anticoagulation, with normalization of the limb perfusion. A nasopharyngeal swab for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by real-time reverse transcription–PCR (rRT–PCR) was negative three times. Haemostasis analysis showed a mild hyperfibrinogenaemia and a shortening of the activated partial thromboplastin time. An extensive screening for cardio-embolism was negative. As the thrombotic event was unexplained, antibody testing for SARS-CoV-2 was performed and the result was positive. Discussion: Venous thrombosis and pulmonary embolisms have been observed in COVID-19. As in our case, the first reports on COVID-19-associated arterial thrombotic events have emerged. A better understanding of the coagulopathy in COVID-19 is essential to guide prevention and treatment of venous as well as arterial thrombo-embolic events.